Quantitative Analysis of Six Phenolic Acids in Artemisia capillaris (Yinchen) by HPLC-DAD and Their Transformation Pathways in Decoction Preparation Process - Fang Tian; Qun-Jia Ruan; Ying Zhang; Hui Cao; Zhi-Guo Ma; Gai-Lian Zhou; Meng-Hua Wu (Journal of Analytical Methods in Chemistry)
We aimed to establish a quantitative analysis method of six constituents (5-caffeoylquinic acid, 3-caffeoylquinic acid, 4-caffeoylquinic acid, 1,3-dicaffeoylquinic acid, 3,4-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid) in Artemisia capillaris (Yinchen) and its decoction by using HPLC coupled with DAD. Besides, the transformation paths of the six constituents were analyzed in decoction preparation processing. The analytical method was fully validated in terms of linearity, sensitivity, precision, repeatability, and recovery and applied to assess the transformation trend and quantitative analysis of the six constituents in Yinchen decoction. The contents of six constituents varied greatly in Yinchen herb and Yinchen decoction, and there were inextricable internal relationships between them. Presumably 3-caffeoylquinic acid was isomerized to generate 5-caffeoylquinic acid and 4-caffeoylquinic acid. Similarly, 1,3-dicaffeoylquinic acid and 3,4-dicaffeoylquinic acid were produced by isomerization of 4,5-dicaffeoylquinic acid. In conclusion, this study provides a chemical basis for quality control of Yinchen decoction, and the changes of selected markers in decoction could give us some novel perspectives to study the relationship between substances and drug efficacy.